2017
DOI: 10.1002/app.44725
|View full text |Cite
|
Sign up to set email alerts
|

Influence of precursor film microstructure on properties of HDPE microporous membranes prepared by stretching

Abstract: Oriented HDPE films having a stacked lamellar morphology were prepared to develop microporous membranes through cast film extrusion followed by stretching. Applying higher draw ratios (DR) and annealing the cast films improved crystal alignments remarkably. It was shown the improvement in c-axis orientation upon annealing was more significant for the films prepared with lower DR. Furthermore, applying Raman spectroscopy, the amorphous mass fraction of the films was obtained. Subsequently, considering a three-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Meanwhile, the appearance of voids sometimes is needed in some special fields, for example, creating microporous separation membranes. [57,58] cases. Cavities can be generated in the interspherulitic regions and inside the spherulites.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Meanwhile, the appearance of voids sometimes is needed in some special fields, for example, creating microporous separation membranes. [57,58] cases. Cavities can be generated in the interspherulitic regions and inside the spherulites.…”
Section: Introductionmentioning
confidence: 74%
“…We emphasize the importance of cavitation triggered at large strain as it can be regarded as a signal to predict the ultimate life of the materials upon stretching. Meanwhile, the appearance of voids sometimes is needed in some special fields, for example, creating microporous separation membranes . Understanding the evolution of cavities during the deformation process can provide the possibility of finding an efficient way to promote, restrain, or even heal the cavities.…”
Section: Introductionmentioning
confidence: 99%
“…In situ study of annealing effect on crystalline structure by SAXS, the crystalline phase thickness, the amorphous region, and the diffusion transition layer of HDPE were increased, and a linear relationship with the logarithm of the annealing time was proposed . In addition, annealing was normally an effective method to improve crystal orientation . Khonakdar and coworkers indicated that annealing increased the free volume as well as the crystal thickness .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, annealing was normally an effective method to improve crystal orientation . Khonakdar and coworkers indicated that annealing increased the free volume as well as the crystal thickness . In general, annealing treatment played a significant role in crystal morphology of casting films and micropores morphology of stretched membranes.…”
Section: Introductionmentioning
confidence: 99%
“…As for dry‐stretching, one of the main issues is to fabricate an appropriate initial row nucleated structure, since the pores are created as a result of lamellae separation . The effective processing parameters in dry‐stretching method including air cooling, roll temperature as well as the time and temperature chosen for annealing process . However, in particle stretching, the pores are formed at the interface of particles and matrix by hot stretching and there is no need to stretch the precursor film at low temperature .…”
Section: Introductionmentioning
confidence: 99%